ENHANCEMENT OF BIODEGRADATION OF HDPE USING SPORULATING MICROORGANISMS - PRIYA, B. JENITA SATHIYA; PRABAKARAN, V.; REENA, D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Microbial enzymes present in soil accelerates biodegradation of polyethylene byhydrolysis reaction leading to weight loss of the plastic strips. Degradation can be monitored using physical and chemical changes by analyzing the final group modifications carried out by FTIR. Three dominant strains of polyethylene degradation are Bacillus cereus, Bacillus licheniformis and Bacillus subtilis. In the present study with Fourier transform infrared spectroscopy pertaining to biodegradation, High Density Polyethylene exhibited a drastic difference recorded between the untreated and treated set of experiments. FTIR analysis indicated that HDPE inoculated with Bacillus licheniformis showed methylene groups and formation of ether group due to the process of degradation. The loss of weight expressed in percentage over a period of twenty days was recorded as 6.93% and 8.5% observed for MSW soil and soil amended with starch. The maximum percentage weight loss was found to be 33% during 120 days of exposure. The study extended on irradiation experiments subjected to UV irradiated HDPE with Bacillus cereus generated new absorption band such as stretching of alkyl groups and vinyl groups occurred due to distortion of the chained HDPE. BATH assay demonstrated that hydrophobicity of Bacillus cereus exhibited 89%. The biodegradation of polyethylene using three different isolates was performed by strum test exhibited 18.02%, 11.88% and 2.06% of degradation respectively.